The successful hybrid team : what the best hybrid teams know about culture that others don't (but wish they did) - Farque, Perrine (John Wiley & Sons Ltd, 2023)
"Written in a friendly, engaging and approachable style, The Successful Hybrid Team will start with an introduction on the changes that are taking place in the workplace and how hybrid work is changing the way teams work. The preliminary chapters will cover how the world of work is rapidly transforming and why culture in hybrid work matters more than ever before. It will then take the readers on an in-depth journey through a four-pillar framework which details what leaders should do to hire, lead and retain a world-class team in a hybrid world. The first pillar describes how to create a unified hybrid leadership team in hybrid work, the second explains how to build extreme clarity and transparency, the third discusses how to over communicate through all channels, and the fourth pillar covers how to unify cross cultural remote teams through cultural awareness. The book will also do a deep dive into topics such as why readers should leverage meetings in a certain way in a hybrid work model, as well as what the most common pitfalls are when it comes to managing teams in hybrid work and how to overcome them. The author will include useful tips and resources throughout the book and a practical checklist supplementing the four-pillar framework"--